Distribution Pattern of Chlorophyll-a in the Delta Wulan Waters, Demak Regency, Central Java, Indonesia - Widianingsih, Widianingsih; Hartati, Retno; Endrawati, Hadi (Universitas Diponegoro, 2024)
The Delta Wulan waters are categorized as estuarine waters, which are greatly influenced by the sedimentation from the Wulan River and Serang River. Besides, the Delta Wulan Waters are vulnerable to the impact of pollution from anthropogenic waste. This research aims to examine the distribution pattern of chlorophyll-a and water quality parameters in the Delta Wulan Waters. Samplings were carried out at 12 stations, which were located in the middle of the Delta Wulan waters. One liter of water samples was taken using a Niskin bottle. The water quality measurements were carried out in situ. The research revealed that the highest chlorophyll-a value was found at Station 11 (2.94 ug/L) in November 2023, and the lowest chlorophyll-a value was also found in November 2023 at Station 6 (0.01 ug/L). Meanwhile, in August 2023, the chlorophyll-a value was in the range of 0.53–8.02 µg/L. The observations in August and November showed that the distribution pattern of chlorophyll-a was regular for stations 1 to 12 (dispersion index value < 1)